Тиббиёт ходимларида касбий деонтологиясини шакллантиришнинг ижтимоий- психологик хусусиятлари - Cобирова, Д.А (SCIENCE and SOCIETY, 2023)
This article highlights the scientific and theoretical foundations of the social deontologiya of health workers and the
Keywords: social competence; social-psychological competence; identification; reflection; altruism